2019
DOI: 10.3892/mmr.2019.9999
|View full text |Cite
|
Sign up to set email alerts
|

ERα and Wnt/β‑catenin signaling pathways are involved in angelicin‑dependent promotion of osteogenesis

Abstract: Reports of the ameliorative effect of angelicin on sex hormone deficiency-induced osteoporosis have highlighted this compound as a candidate for the treatment of osteoporosis. However, the molecular mechanisms of action of angelicin on osteoblast differentiation have not been thoroughly researched. The aim of the present study was to evaluate the effect of angelicin on the proliferation, differentiation and mineralization of rat calvarial osteoblasts using a Cell Counting Kit-8, alkaline phosphatase activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Hence, potential compounds that could upregulate the body's estrogen levels are needed. The treatment of MC3T3-E1 cells and primary rat osteoblast cells with angelicin increased the expression of ERa protein (Ge et al, 2018;Ge et al, 2019). A similar increase in ERa by angelicin in the grey matter of ventral and dorsal horns were also reported in adult male C57BL/6 mice that had suffered spinal cord injury (Li et al, 2017a).…”
Section: Angelicin As An Osteogenesis and Chondrogenesis Enhancersupporting
confidence: 61%
See 3 more Smart Citations
“…Hence, potential compounds that could upregulate the body's estrogen levels are needed. The treatment of MC3T3-E1 cells and primary rat osteoblast cells with angelicin increased the expression of ERa protein (Ge et al, 2018;Ge et al, 2019). A similar increase in ERa by angelicin in the grey matter of ventral and dorsal horns were also reported in adult male C57BL/6 mice that had suffered spinal cord injury (Li et al, 2017a).…”
Section: Angelicin As An Osteogenesis and Chondrogenesis Enhancersupporting
confidence: 61%
“…To determine the involvement of Wnt/b-catenin signaling pathway, the cells were co-treated with both angelicin and DKK-1, an antagonist to the pathway. The results obtained revealed that DKK-1 successfully attenuated the effect angelicin had on the cells (Ge et al, 2019). Besides that, Zhang and Ta (2017) also studied the effect of angelicin on TGF-b1 reporter gene activity using transfected HEK293T cells.…”
Section: Angelicin As An Osteogenesis and Chondrogenesis Enhancermentioning
confidence: 94%
See 2 more Smart Citations
“…Angelica is gaining ground all over the world, including Europe, North American and Southeast Asia. In folk medicine, angelica is believed as an anti-inflammatory, anti-aging medicine with wide use ( Wei et al, 2016 ; Ge et al, 2019 ). Angelicin is isolated from Angelica Sinensis considered as an anti-frostbite, analgesia, hemostasis active ingredients.…”
Section: Introductionmentioning
confidence: 99%